Dermoscopy for Tick Bite: Reconfirmation of the Usefulness for the Initial Diagnosis - Masahiro Matsuda; Naoki Oiso; Yasuhiro Yano; Akira Kawada (Karger Publishers, 2011)
Ticks transmit a variety of infectious diseases. Diagnosis requires verification of a tick's presence. Here, we describe a 61-year-old woman bitten by an eight-legged nymphal Amblyomma testudinarium. We re-emphasize the usefulness of dermoscopy for identifying signs of the bite and determining the species of the biting tick.